Political Culture of the Habsburg Peoples in the Mid-19th and Early 20th Centuries. Review of: Vashhenko, M. S., Velichko, O. I., Dronov, M. Yu., et al. (2018). Politicheskie partii i obshhestvennye dvizheniia v monarkhii Gabsburgov, 1848–1914 gg.: ocherki [Political Parties and Social Movements in the Habsburg Monarchy, 1848–1914: Essays]. Moscow: Indrik. 408 p - But, Yulia E. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2021)
This review characterises the content and comments on the importance of a collective monograph which can be regarded as the first comprehensive work in the Russian historical science to depict the dynamics of political culture and the stages of party building by almost all the peoples of the multinational Habsburg monarchy in 1848–1914. In a series of essays, the authors demonstrate how Habsburg peoples fought, though with a varying degree of ardour and success, for the recognition of their collective identity and claimed to be recognised as collective subjects of the state. The review reveals the main issues that thwart drawing a comprehensive review of the political culture of the peoples of the monarchy resulting from the composite state structure, the nature of political associations and parties, and the different development stages of the national idea. The authors revise the teleological approach of 20th-century historiography which can be considered a novelty in the Central European studies in Russia. Yet, the book contains occasional weaknesses in the chains of reasoning and evidence. Nonetheless, the strengths of the book make it possible to rank it among the authoritative books on the Central European history of the modern period.